The use of historical evidence of the Tamiang kingdom on the east coast of Aceh as a source for learning local history for high school students - Usman, Usman; Akob, Bachtiar; Rahmatsyah, Rahmatsyah; Zakaria, Nurhijrah Binti (Jurnal Ilmu Pendidikan, 2023)
The Tamiang Islamic Kingdom is one of the oldest kingdoms on the east coast of Aceh, bordering Haru Bay and Kampai Island of Pangkalan Susu. Its north serves as the front line of defense in the Malacca Strait, part of the sovereignty of the Samudra Pasai Islamic Kingdom, in the 12th century AD. In 1350, the country of Tamiang faced the challenge of the expansion of Majapahit commandeered by Patih Gaja Mada, who wanted to unite all regions in the archipelago following the "Palapa Oath" during the authority of King Hayam Wuruk Mahapatih Ratu Tribhu-wanatunggadewi. This study used a descriptive qualitative research method, then collected data through literature study, document analysis, and utilizing historical evidence of the Tamiang kingdom on the east coast of Aceh. The results showed that the students' poor skills in reading and analyzing historical sources were due to the lack of usage of historical evidence as a source of local history learning. Therefore, this research also contributes to the adoption of historical evidence of the Tamiang kingdom on the east coast of Aceh as a historical learning source for high school students to improve the Use of Primary Source Evidence skills.